2019
DOI: 10.1371/journal.pone.0215181
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity, femininity, and leadership: Taking a closer look at the alpha female

Abstract: An extensive review and textual analysis of the academic and popular literature of the human alpha female was conducted to examine the social construction and expression of the alpha female identity in a small non-random sample of North American women (N = 398). This review revealed 2 predominant alpha female representations in the literature–one more masculine versus one more feminine–and 21 alpha female variables. In this sample of women, the “alpha female” was found to be a recognized socially constructed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 88 publications
(171 reference statements)
0
16
0
Order By: Relevance
“…Recently, Sumra [40] conducted an extensive review and textual analyses of the academic and popular literature of the human alpha female to examine the social construction and expression of the alpha female identity in a small non-random sample of North American women (N=398). In that study [40], participants completed a 96-question survey and were asked questions in the end of this survey about the alpha female identity. Participants could not go back to change their answers.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Sumra [40] conducted an extensive review and textual analyses of the academic and popular literature of the human alpha female to examine the social construction and expression of the alpha female identity in a small non-random sample of North American women (N=398). In that study [40], participants completed a 96-question survey and were asked questions in the end of this survey about the alpha female identity. Participants could not go back to change their answers.…”
Section: Methodsmentioning
confidence: 99%
“…That review revealed 2 predominant alpha female representations in the academic and popular literature – one more masculine versus one more feminine – and 21 variables likely to be associated with the expression of the alpha female identity. That study [40] found that the alpha female was a recognized socially constructed female identity. Univariate analysis revealed positive and highly significant differences in self-reported mean scores between alpha (N=94) and non-alpha (N=304) females for 10 variables related to expression of the alpha female identity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations